Characteristics and outcomes of chronic pulmonary aspergillosis: a retrospective analysis of a tertiary hospital registry. (17th February 2014) - Camara, Boubou; Reymond, Emilie; Saint‐Raymond, Christel; Roth, Hubert; Brenier‐Pinchart, Marie‐Pierre; Pinel, Claudine; Cadranel, Jacques; Ferretti, Gilbert; Pelloux, Hervé; Pison, Christophe; Grenoble Aspergillus Committee
Abstract Introduction Our objective was to investigate characteristics risk factors and outcomes of patients with chronic pulmonary aspergillosis (CPA). Methods The Aspergillosis Committee prospectively collected Aspergillus notifications from January 2000 to December 2011. A retrospective analysis of data was performed. Results Among 1614 notifications registered, 44 cases of CPA in non‐immunocompromised patients were identified. The median age was 65 years (Q1–Q3: 54–75), the median body mass index (BMI) was 20 kg/m2 (Q1–Q3: 16–22) and 15 had chronic obstructive pulmonary disease. All patients had a positive specific serum precipitin antibody titer. Radiological presentations were: cavitations [single n = 31 (70%); multiple n = 12 (27%)] containing mycetomas [n = 18 (41%)], consolidations [n = 19 (43%)], emphysema [n = 15 (34%)] and sequelae of mycobacterial infection [n = 10 (23%)]. The median duration of follow‐up was 30 months (Q1–Q3: 14–55). The median duration of antifungal treatment was 6 months (Q1–Q3: 3–12). Outcomes were unfavorable in 14 patients, and 12 (27%) died. Analysis by multivariate Cox regression model with bootstrapping showed that a higher BMI and a lower Charlson index score were predictive of favorable evolution, hazard ratio (95% confidence interval): BMI (+1) = 0.83 (0.71–0.97), Charlson (+1) = 1.37 (1.01–1.85). When analyses were restricted to chronic CPA and chronic necrotizing pulmonary aspergillosis, the multivariate Cox regression model showed that both BMI and Charlson index score were not statistically significant. Conclusion Our results provide data on clinical characteristics and outcomes of CPA emphasizing the role of preexisting chronic respiratory conditions and protective effect of preserved BMI and lower Charlson index score.